Cell-based evaluation of a novel Dictyophora indusiata polysaccharide against oxidative-induced erythrocyte hemolysis - Liao, W; Chen, L; Yu, B; Lei, Z; Wu, X; Yang, J; Ren, J (Cellular and Molecular Biology, 2016)
The protective effectof a polysaccharide from Dictyophora indusiata(DP1)against oxidative hemolysis was comprehensively evaluated. The 2, 2-azobis (2-amidino-propane) dihydrochloride (AAPH)-induced erythrocyte hemolysis assay showed that DP1 exhibited excellent anti-hemolytic activity(87.4% hemolysis suppression ratio at 20 nmol/mL). Also, the formation of conjugated diene induced by cupric chloride (CuCl2) in plasma was significantly inhibited by DP1. Besides, DP1 could effectively inhibit AAPH-induced overproduction of reactive oxygen species (81.5 % inhibition at 20 nmol/mL) and alleviated the enhancement of intracellular antioxidant enzymes including superoxide dismutase(SOD), glutathione peroxidase (GPX) andcatalase (CAT) activities. Also, the malondialdehyde (MDA) formation caused by oxidative stress was suppressed by 57.0% at DP1 concentration of 20 nmol/mL. Taken together, the possible intracellular antioxidant detoxifying mechanism of DP1 was probably via preserving the activities of the antioxidant enzymes (SOD, GPx and CAT) as well as inhibiting lipid peroxidation, and thus alleviated erythrocytes oxidation and plasma oxidation.